(untitled) (Olhar de Professor, 2023)
The Pedagogical Residency Program is a federal government initiative, under the governance of the Coordination and Improvement of Higher Education Personnel (Capes). The purpose of the program is to promote institutional projects designed specially for the initial training of basic education teachers in undergraduate courses. This text has the following objective: to present an account of the experience carried out within the scope of the Pedagogical Residency Program, linked to the State University of Piauí (UESPI), in the Pedagogy course at Campus Jesualdo Cavalcanti, in the area of Literacy. Composition of the subproject nucleus: 1 area coordinator (teacher at UESPI); 1 preceptor (professor of the municipal public school system); 8 residents (students of the pedagogy course at UESPI). The total workload was 414 hours, distributed in three modules, planned and executed considering increasing levels of complexity. The results of this experience allow us to make some observations, such as: training of the licentiate, considering the link between theory and practice; encouragement and appreciation of the literacy teacher; promotion of actions in rural schools, with the support of the management team and the teaching team, to encourage the learning and development of children in early childhood education; stimulus, through daily activities and reading projects, for the improvement of the literacy process and for the formation of a literary education.